Intergenerational transfers and informal care for disabled elderly persons in China: evidence from CHARLS. (9th March 2017) - Liu, Xiaoting; Lu, Bei; Feng, Zhixin
Abstract: Aiming at 'ageing healthier and ageing better', a certain amount of high‐quality informal care should be available for elderly persons with physical disability as formal care is barely accessible in China. The demographic transition and family structural changes have dramatically weakened traditional norms of filial piety and the structure of intergenerational transfers. This article employed nationwide representative data from the first wave (2011) of Chinese Health and Retirement Longitudinal Study (CHARLS) in order to identify the duration of informal care provision at home for frail elders (1122 in rural areas and 577 in urban areas, total 1699), measured in monthly hours, before estimating the associations between intergenerational transfers and the received time of informal care with Tobit Model analysis. Results showed that financial support from the younger generation was unexpectedly negatively associated with the monthly hours of care, implying a reduction of caring support along with increasing financial transfers towards older parents. The lack of informal care could not be compensated by having more children, co‐residing with children, or increasing the parent‐to‐child/grandchild transfers. Spouses were shown to replace children as the major caregivers. In addition, the community‐based long‐term care system needs to be promoted to sustain and develop informal care, as the latter will become increasingly important with changing family dynamics. Finally, the received time of informal care, rather than the severity of physical disability measured by difficulty with ADLs or IADLs, was introduced to identify the actual demand for care by elders. The paper argues that it is important to reconceptualise and re‐investigate the duration of care provision in the Chinese context in order to develop standards of payment as part of long‐term care policies.